False Positive Fourth Generation HIV Screening Tests in Low Prevalence Areas of Saudi Arabia: A Case Study and Literature Review - Ngozi Virginia Aikpokpo; Ahmed YAHYA Omaysh (Medical Science: Trends and Innovations Vol. 7, 2025)
Introduction: HIV screening tests are routinely conducted on dialysis patients as the constant exposure of their blood during the dialysis process makes them a reasonable risk for blood-borne infections. However, in low prevalence settings, where HIV rates are <0.1% of the population, false positive results are more likely. In low prevalence areas, the positive predictive value (the probability of a positive result being truly positive) decreases drastically. This results in apprehension in the dialysis unit as breaches in infectious disease protocols could be presumed. It may also contribute to psychological distress for both the patient and caregivers. This is illustrated in the case report below. Case Summary: A 62-year-old male Saudi end-stage kidney disease patient secondary to DM nephropathy began dialysis a year before presentation in a hemodialysis center in Saudi Arabia. Routine screening tests done at the start of dialysis revealed negative Hepatitis C, HIV 1 and 2 screening but a positive Hepatitis B surface antigen screen. The patient went for holiday dialysis at another facility and had a routine fourth-generation HIV test done which was positive. A confirmatory HIV PCR test was negative. Conclusion: This case highlights the need for caution in interpreting highly sensitive and specific HIV screening tests in a low-prevalence setting. Routine screening beyond the national recommendation may not be necessary in low-prevalence areas. When screening is indicated, positive results must be followed by confirmatory tests. Thus, it may be prudent to avoid conducting routine highly sensitive and specific HIV screening tests in hemodialysis centers with low prevalence rates than what is recommended to reduce the waste of resources.